Portret idealnej królowej w antycznej powieści greckiej – w stronę modelu - Cieśluk , Małgorzata (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
This article line of reasoning follows the assumption that in the period in which the ancient Greek novel was developing there already existed fixed cultural norms which thus provided for the frames of the then literary presentations of women in power. In Callirhoe by Chariton or Aethiopica by Heliodorus the reader comes across three images of queens and can consequently ponder over the most significant elements of the model of an ideal female ruler. The comparative analysis of the three heroines in question as well as the juxtaposition of their images with the remaining female characters of Greek novels thus constitutes the core of the article.